Audit Kelistrikan pada Gedung Administrasi Niaga (AB) dan Akuntansi (AC) Politeknik Negeri Malang - Ahmad Hermawan; Roby Tri Stya Hutama; Budi Eko Prasetyo; Candra Wiharya (Elposys: Jurnal Sistem Kelistrikan, 2021)
This study aims to analyze the average consumption of electrical energy and the Intensity of Energy Consumption (IKE)and the effect of temperature of electrical equipment in the main panel of the AB and AC buildings on the applicable electrical standards in the AB and AC buildings of Politeknik Negeri Malang. From the research, the results of the average consumption of electrical energy in each building are 2591.96 kWh and 1799.74 kWh per month, the value of Energy Consumption Intensity (IKE) is 34.55 kWh / m2 and 34.11 kWh / m2, both results fall into the category of energy use. very efficient, all the equipment in the panels of the two buildings is in good condition according to the PLN SK DIR 520 2014 book, the highest temperature value of the safety equipment is 32.8 ᵒC at NH Fuse T. this is due to the current flowing of 34.29A, the value of the equipment with the lowest temperature of 27.8 C on MCB C16 with a maximum standard of 45 C, the current conductive capacity is still in accordance with using a 2.5 mm2 cable with KHA 46 A, while the load current for each branch is protected by MCB 10 A. For cooling in rooms that use AC The split is 28,000 BTU / hour and it is still below the standard of 38,000 BTU / hour